Equine chorionic gonadotropin drives the transcriptional profile of immature cumulus-oocyte complexes and in vitro-produced blastocysts of superstimulated Nelore cows - Franchi, Fernanda Fagali [UNESP]; Satrapa, Rafael Augusto [UNESP]; Fontes, Patrícia Kubo [UNESP]; Santos, Priscila Helena [UNESP]; Razza, Eduardo Montanari [UNESP]; Emanuelli, Isabele Picada [UNESP]; Ereno, Ronaldo Luiz [UNESP]; Mareco, Edson Assunção; Nogueira, Marcelo Fábio Gouveia [UNESP]; Barros, Ciro Moraes [UNESP]; de Souza Castilho, Anthony César (Wiley, 2019)
Studies have shown that the use of equine chorionic gonadotropin (eCG), which binds both follicle stimulating hormone (FSH) and luteinizing hormone (LH) receptors, could modify the female reproductive tract. We, thus, aimed to quantify the messenger RNA (mRNA) abundance of genes related to cumulus-oocyte complexes (COCs) and embryo quality in Nelore cows (Bos taurus indicus) submitted to ovarian superstimulation using only FSH (FSH group; n = 10) or replacement of the last two doses of FSH by eCG (FSH/eCG group; n = 10). All animals were slaughtered and the ovarian antral follicles from both groups (10–14 mm in diameter) were aspirated for cumulus, oocyte and in vitro embryo production gene expression analysis. The relative mRNA abundance of 96 genes related to COCs development and embryo quality was measured by RT-qPCR. We found that oocytes are more affected by eCG use and that 35 genes involved in lipid metabolism, oxidative stress, transcriptional control, and cellular development were upregulated in the FSH/eCG group. In blastocysts, lipid metabolism seems to be the main pathway regulated by eCG use. We suggest that these multiple effects could be due to the ability of eCG to bind LHR and FSHR, which could activate multiple signal transduction pathways in the superstimulated ovary, further impacting the transcriptional profile of COCs and blastocysts.
Keywords: bovine; gene expression; hyperstimulated ovary; hyperstimulation; multiple ovulations